The Impact of Work-Famıly Enrıchment on Work Engagement: Examınıng the Medıatıng Roles of Job Satısfactıon and Self-Effıcacy - Puspitawati, Ni Made Dwi; Kanadjo, Leni Marlina; Suliati, Ni Nyoman; Yudhaningsih, Ni Made (Department of Management, Faculty of Economics and Business, Brawijaya University, 2024)
This research examines the effect of work-family enrichment on work engagement through self-efficacy and job satisfaction as mediating variables among women entrepreneurs in Bali. Data was collected through questionnaires distributed to women entrepreneurs in Bali. The research sample consisted of women entrepreneurs in Bali, 183 people using the snowball sampling technique. The results of data analysis using PLS show that there is a positive influence of work-family enrichment on self-efficacy, job satisfaction, and work engagement. In addition, self-efficacy and job satisfaction have also been proven to be significant mediators in the relationship between work-family enrichment and work engagement. If women entrepreneurs feel that positive experiences at work enrich their family life, they will believe in their ability to complete tasks and increase their satisfaction in their work, leading them to be more engaged in the organization. The managerial implication of these findings is the importance of women entrepreneurs in creating a work environment that supports a balance between work and family life, which can increase their self-efficacy, job satisfaction, and work engagement. This research contributes to the literature on work-family enrichment and work engagement, especially in the context of women entrepreneurs in Bali.